Administrative Records for Information and Local Public Policy Systems - Lema Changoluisa, Katy (2022)
The data revolution and the need to generate information in real time is an ongoing demand, even more so for public institutions that are bound to keep their management processes transparent. Having a local information system allows GADs (Autonomous Decentralized Governments) to display their actions via data, as well as having a tool that strengthens the efficiency of their management and generates evidence based in timely, quality information to implement planning, follow-up and monitoring processes towards their objectives and goals as presented in their governance plans. The daily activities of GADs must be backed up with information that can be shown through institutional administrative records as a main source of data and information to show and keep their governance actions transparent. Local information systems (SIL) allow for the organization of data and information in the GADs themselves and help keep their achievements transparent in the territory. GADs, both at the province and canton level, are legally bound to ensure their proper implementation. Thus, an analysis was made on the web pages of theGADs to review their existence, progress and fulfilment of the corresponding regulations for SILs. At this time, only 9 of the 24 provincial GADs have started this process